Realizing Responsible and Sustainable Living: Implementation and Outcomes of Water Conservation Efforts in Sidomulyo Village, South Sumatra - Humaira; Maulana Rizky Wijaya; Syauqi Ridlo Robbiy (Prospect Publishing, 2024)
The international forum, World Water Forum 2024, held in Bali, emphasized the global threat of a potential crisis in the availability of sustainable clean water. This issue is not limited to developing countries but will be felt across the world. This event is a form of social responsibility by PT Pertamina Gas (Pertagas) Operation South Sumatra Area (OSSA) in collaboration with the community of Sidomulyo Village as the subject of this service. Various activities were conducted involving the community, listening to their aspirations, formulating solutions together with the community, implementing the initiatives with them, and carrying out monitoring and evaluation collectively. This water conservation effort with the community is encapsulated in a program slogan called Pusaka Tirta. Pusaka Tirta stands for the strengthening of sustainability strategies, with Tirta meaning water. Furthermore, this slogan has been broken down into three sub-programs that are categorized based on the types and groups of activities. First, the water conservation efforts that focus on adaptation are named Tirta Asasta. Then, the conservation efforts focusing on mitigation are called Tirta Mahardika. Lastly, the conservation efforts focusing on rehabilitation are named Tirta Amarta.